Amphotericin B deoxycholate nasal spray administered to hematopoietic stem cell recipients with prior fungal colonization of the upper airway passages is associated with low rates of invasive fungal infection. Issue 1 (14th January 2015) - Trifilio, S.M.; Heraty, R.; Zomas, A.; Zhou, Z.; Fong, J.L.; Liu, D.; Zhao, C.; Zhang, J.; Mehta, J.
Abstract Background Invasive fungal infections cause major problems during hematopoietic stem cell transplantation (HSCT). Fungal colonization of the upper airway passages occurs frequently, and may serve as a portal of entry for potentially life‐threatening fungal infections, especially in immunocompromised patients. Methods A clinical practice was instituted at Northwestern Memorial Hospital in Chicago in 2005, to administer amphotericin B deoxycholate nasal spray (ABNS) 0.5% to all HSCT recipients with fungal colonization of their nasal passages, in addition to standard oral antifungal prophylaxis. Results Among 1945 HSCT patients treated during the study period, 109 patients were identified with positive fungal surveillance cultures. Conclusion Breakthrough fungal infections occurred in only 2 patients (2%), thus in this select group of HSCT recipients, ABNS administration is associated with a very low rate of breakthrough infection.